Integrated SWOT–QSPM Approach to Determine Key Strategies in Agroindustry Development - Agustin Rani Nurfadila; Palmadi Putri Surya Negara; Astari Ratnaduhita; Riska Sumirat; Ilham Wahyudi; Ilham Perdana (Agroindustrial Technology Journal, 2026)
CV ABC is a food business that produces amplang crackers made from fish and faces challenges in business development amid increasing competition. This study aims to formulate appropriate business development strategies through an analysis of the company's internal and external factors. The qualitative descriptive approach with data collection through interviews, observations, and document studies were applied in this study. Data analysis is carried out using the SWOT method to identify strengths, weaknesses, opportunities, and threats, as well as the Quantitative Strategic Planning Matrix (QSPM) method to determine priority strategies for business development. SWOT analysis results show that CV ABC main strengths include a widely recognized brand, an efficient distribution network, consistent product quality, and halal certification. The weaknesses faced include limited product diversification, suboptimal utilization of production technology, and limited human resources. Business opportunities come from the increasing demand for cracker products, government support for food MSMEs, as well as developments in digital marketing, while the main threats include competition from similar products, fluctuations in raw materials, and changes in consumer preferences. The results of the QSPM analysis was indicate that the strategy of developing product diversification based on flavor and packaging innovation is the top priority strategy, followed by the strategy of strengthening and expanding the market through brand optimization and digital marketing. This strategy is expected to enhance competitiveness and business sustainability.